Prognosis of MGMT-Positive Gene in Patients with Brain Tumors of Grade III and Grade IV - Rajendra, Ishitaa; Dhal, Shikha; Goyal, Sumit; Tyagi, Surabhi; Sharma, B. S.; Yadav, Ajay; Yadav, Dinesh (South Asian Journal of Cancer, 2023)
Objective To evaluate MGMT gene positivity is associated with better survival in patients diagnosed with brain tumor World Health Organization (WHO) grades III and IVMaterial and Methods Single-institute restrospective study. A total of 80 patients were enrolled, all underwent surgery either total or subtotal excision of the tumor and MGMT gene testing on tumor tissue by RT-PCR. All received adjuvant radiation (60 Gy/30 fractions, 5 fractions/week) with concurrent temozolomide (75 mg/m2), followed by 12 cycles of adjuvant temozolomide (150 mg/m2 1st cycle followed by 200 mg/m2) with regular follow-up.Results A total of 80 patients, 75 underwent subtotal excision, 27 were WHO grade III vs. 48 WHO grade IV. Five underwent total excision 1 was WHO grade III vs. 4 WHO grade IV. The median PFS and OS in five patients in total excision in grade III patient was 9.0 and 20 compared with Grade IV, where the median PFS and OS was 8.8 and 17.8 months. Out of 75 patients in the subtotal group median PFS and OS, respectively, in Grade III group was 9.1 and 19.3 and, WHO grade IV with median PFS of 8.8 and OS of 18.8.Conclusion MGMT gene positivity is a prognostic factor in grade III and IV brain tumor.
Keywords: brain tumor; excision; grade III and IV; MGMT; temozolomide